PENDEKATAN PEMBELAJARAN KONTEKSTUAL SETTING LESSON STUDY DALAM MATA KULIAH KALKULUS - I Wayan Eka Mahendra (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
This study aims to determine significant differences between students’ calculus achievement who follow contextual teaching and learning approach setting lesson study and who follow conventional approach. The population in this study were all students of the first semester of the department of mathematics education IKIP PGRI Bali academic year 2015/2016, with a sample of 57 students' taken by simple random sampling technique. This study is an experimental research (quasi experimental) with non-equivalent control group design. Data of calculus achievement was collected using calculus achievement test. The data was then analyzed using t-test. The results of this study indicate that there are significant differences between students’ calculus achievement who follow contextual teaching and learning setting lesson study and who follow conventional approach of the department of mathematics education IKIP PGRI Bali academic year 2015/201.